STUDY OF THE VARIATION OF LOW LEVEL MOISTURE AND ITS RELATION TO CONVECTIVE ACTIVITY BASED ON GPS DATA OBSERVATION - KRISTIANTO , ARIES
Low Level Moisture (LLM) plays an important role in determining the instability of the troposphere and the mechanism of air parcelsÃ‚Â’ rise to the growth of the cloud. The conventional water vapor observation techniques cannot detect LLM directly.However, recent developments on Global Positioning System (GPS) satellite data processing make it possible to estimate the total moisture content in an atmospheric column as Precipitable Water Vapor (PWV) with better spatial-temporal resolution;and its observation is continuous and near real time. In this study, we developed a simple but effective technique to extract LLM based on GPS data, in which the upper-level PWV is estimated from the European Centre for Medium-Range Weather Forecasts (ECMWF) and then subtracted from the total PWV, by assuming that the height of LLM in fixed layer (method I) and in variable layer (method II). Then correction was conducted by comparing the specific humidity with the model ECMWF and radiosonde (rason) observations were used for estimating the water vapor vertical profile.The result of the first method has limitations because LLM is assumed to be in a fixed layer. Therefore, the correction method was developed by using Zenith Total Delay (ZTD) and PWV from GPS observation, thereby producing the height of variable layers (ZLLM) as a parameter that can better indicate the vertical movement of water vapor, which is directly related to the process of convection and able to be used to estimate the vertical profile of water vapour. The result of sensitive tests showed a strong correlation and a small error so that the initiation of specific humidity from the interpolation of ECMWF data can be used to estimate the vertical humidity profile. Diurnal variation of LLM can reveal the characteristic of moisture content change in the atmosphere. Fluctuation of the diurnal variation pattern of ZLLM can be interpreted as the effect of the variation of water vapor, and ZLLM is possible to be used as an index of atmospheric instability to monitor convective activity.iv The general pattern of PWV variation during 2009 follows the seasonal pattern of monsoon rainfall. The time difference of maximum value of LLM is associated with the influence of the intrusion of sea breeze from the north coast of Java (especially in the dry season) referring to shifting pattern of maximum the LLM event, i.e. slower in the dry season and faster in the rainy season. This agrees with the results of previous studies. Madden Julian Oscillation (MJO) activities affect the diurnal variation of LLM spatially and temporally. On pre-MJO, LLM concentrations in the western part of Java were generally low from morning to evening, LLM increased only in the late afternoon to the evening, which was not too significant. When MJO was in active mode, the increase of LLM coincided with the timing of convective processes from the morning to the afternoon. The highest variation of LLM spatially was located in the northern and southern parts of western Java. At post-MJO, LLM reduced gradually indicated by low LLM and increased LLM concentration toward the central and eastern regions in line with the MJO propagation. In general, the conclusion of this study is as follow: LLM can be extracted by the combination of GPS data and the ECMWF global model, and furthermore it can also be used to estimate the vertical profile of water vapor.